Disfungsi Peraturan Perundang-Undangan Tanggung Jawab Sosial dan Lingkungan di Indonesia - Lego Karjoko; Josephine Santosa; I Gusti Ayu Ketut Rachmi Handayani (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This study is aimed to analyse various Indonesian national regulations that govern about the implementation of social and environmental responsibility (SER) in the actualisation of its objectives for the equitable distribution of natural resources in Indonesia. The analysis is undertaken in terms of the phrases used, the subjects who are obliged to perform SER, the funding sources, the allocation of the funds, the instructed programs, as well as the course of the SER itself. By using normative legal research, this study concludes that the existing regulations have not consistently governed the implementation and standards of SER as expected by the Government. Additionally, according to Fuller, this kind of multi-interpretation will result in the malfunction of legal products, and ultimately frustrate the achievement of the SER objectives. On this matter, it is proposed that the Indonesian government needs to formulate a regulation that comprehensively and specifically govern about the SER to become a guideline for all the existing stakeholders.